Exploring Emotional Intelligence and College Adjustment in Final-Year College Students - Caesarania, Nadiva Marsha; Witriani, Witriani; Harding, Diana (Jurnal Paedagogy, 2024)
This study aims to analyze the relationship between the dimensions of college adjustment and domains of emotional intelligence among final-year students (7th semester) with the Merdeka Belajar Kampus Merdeka (MBKM) curriculum. This research used a correlational method with a non-experimental quantitative approach. The study respondents were final-year students of the Faculty of Psychology, Padjadjaran University, who participated in MBKM activities outside the university during the sixth semester and resumed regular classes during the seventh semester. Among 72 eligible students, 67 participated in the study. The instruments used to measure college adjustment and emotional intelligence were the translated version of Student Adaptation to College Questionnaire (SACQ) and an instrument based on Goleman's emotional intelligence theory, respectively. Correlation tests were conducted using the Pearson Product Moment. The findings revealed a significant positive correlation between college adjustment and emotional intelligence (r = 0.410, p < 0.05). Furthermore, the analysis proved correlations among certain dimensions of college adjustment and domains of emotional intelligence. The implications highlight the role of MBKM activities in enhancing students' skills to support their adaptation and emotional intelligence.